A Development Model Of Promotional Strategy, Brand Equity, And Product Innovation Influencing Purchase Intention: A Case Study Of Nata De Coco MSMEs In North Minahasa Regency, Indonesia - Silvya Lefina Mandey; Victor Paskah Kalawat Lengkong; Jenny Emma Agustin Kandou (PT Inovasi Pratama Internasional, 2026)
Research on promotional strategies, brand equity, product innovation, and purchase intention in marketing is a crucial area of study. This research aims to enhance marketing strategies, particularly for MSMEs producing nata de coco in North Minahasa Regency, in supporting and improving their business processes. The study utilizes a sample drawn from the population. Given the large size of the population and the impracticality of studying the entire group, a sample size of 100 respondents was selected, meeting the minimum requirements for sampling. This research employs a causal associative approach to analyze the relationships among variables, both simultaneously and partially. The variables examined in this study include: promotional strategy (X1), measured through indicators such as promotional messages, promotional media, and timing (Kotler & Keller, 2016); brand equity (X2), measured by brand awareness, perceived quality, brand association, and brand loyalty; and product innovation (X3), with indicators including transactional interest, referential interest, preferential interest, and exploratory interest. The results of the study indicate that promotional strategies, brand equity, and product innovation have both partial and simultaneous (combined) effects on the purchase intention of nata de coco MSME products in North Minahasa Regency.